High Triplet Energy Host Materials for Blue TADF OLEDs—A Tool Box Approach - Rodella, Francesco; Bagnich, Sergey; Duda, Eimantas; Meier, Tobias; Kahle, Julian; Athanasopoulos, Stavros; Köhler, Anna; Strohriegl, Peter (Frontiers in Chemistry, 2020)
The synthesis of stable blue TADF emitters and the corresponding matrix materials is one of the biggest challenges in the development of novel OLED materials. We present six bipolar host materials based on triazine as an acceptor and two types of donors, namely, carbazole and acridine. Using a tool box approach, the chemical structure of the materials is changed in a systematic way. Both the carbazole and acridine donor are connected to the triazine acceptor via a para- or a meta-linked phenyl ring or are linked directly to each other. The photophysics of the materials has been investigated in detail by absorption-, fluorescence-, and phosphorescence spectroscopy in solution. In addition, a number of DFT calculations have been made which result in a deeper understanding of the photophysics. The presence of a phenyl bridge between donor and acceptor cores leads to a considerable decrease of the triplet energy due to extension of the overlap electron and hole orbitals over the triazine-phenyl core of the molecule. This decrease is more pronounced for the para-phenylene than for the meta-phenylene linker. Only direct connection of the donor group to the triazine core provides a high energy of the triplet state of 2.97 eV for the carbazole derivative CTRZ and 3.07 eV for the acridine ATRZ. This is a major requirement for the use of the materials as a host for blue TADF emitters.